A New Model for Student Support in High-Poverty Urban Elementary Schools: Effects on Elementary and Middle School Academic Outcomes. (August 2014) - Walsh, Mary E.; Madaus, George F.; Raczek, Anastasia E.; Dearing, Eric; Foley, Claire; An, Chen; Lee-St. John, Terrence J.; Beaton, Albert
Efforts to support children in schools require addressing not only academic issues, but also out-of-school factors that can affect students' ability to succeed. This study examined academic achievement of students participating in City Connects, a student support intervention operating in high-poverty elementary schools. The sample included 7, 948 kindergarten to fifth-grade students in a large urban district during 1999–2009. School- and student-level treatment effects on report card grades and standardized test scores in elementary through middle school were estimated. Propensity score methods accounted for pre-intervention group differences. City Connects students demonstrated higher report card scores than comparisons and scored higher on middle school English language arts and mathematics tests. This study provides evidence for the value of addressing out-of-school factors that impact student learning.